Testing a conservation compromise: No evidence that public wolf hunting in Slovakia reduced livestock losses - Kutal, Miroslav; Duľa, Martin; Royer Selivanova, Alisa; López-Bao, José V. (Conservation Letters, 2024)
© 2023 The Authors. Conservation Letters published by Wiley Periodicals LLC. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited. Variation in the legal status and management of wolves (Canis lupus) across EU Member States provides a good opportunity to test the effectiveness of different practices to reduce livestock losses. This opportunity for testing is particularly useful for lethal interventions, as they are among the most controversial actions within the large carnivore management toolbox. We aimed to test a conservation compromise adopted in Slovakia, based on a public wolf-hunting scheme and annual hunting quotas between 2014 and 2019, and partially justified to reduce livestock losses. We assessed whether this hunting scheme influenced livestock depredation levels (at the district level). Wolves in the area fed mainly on wild ungulates (98.9% of consumed biomass). While domestic sheep comprised only 0.5% of the diet, they were dominant among the reported livestock killed by wolves (91.1%). Using two different approaches, we did not observe a relationship between the number of killed wolves and livestock losses. Alternatively, a negative relationship between wild prey biomass and livestock losses was found. Since 2021, public wolf hunting has not been conducted in Slovakia, and there is no merit in the previous justification for this conservation compromise to reduce livestock losses. Regional Government of Asturias (GRUPIN research grant), Grant/Award Number: AYUD/2021/51314; Spanish Ministry of Economy, Industry and Competitiveness, Grant/Award Number: CGL2017-87528-R AEI/FEDER EU. Peer reviewed